Analisis Pendapatan Melon (Golden Alisha) Pada Kelompok Tani “Le Padi Sabee” di Desa Mns. Dayah Kecamatan Peusangan Kabupaten Bireuen - Zafira, Nada; Khumaira, Khumaira; Puspita, Diah Eka (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
Penelitian Melons are one of the agricultural commodities that are very promising to cultivate. Apart from their high selling price, demand for melons in Aceh is also increasing from year to year. The aim of the research is to determine the income of melon farming and the profit or worth of farming and to determine the marketing channels and margins in Mns.Dayah Village, Peusangan District, Bireuen Regency. The research method used was a quantitative method and the sampling technique used a census sampling technique with a sample of 10 melon farmers. The data analysis model used is revenue analysis, R/C Ratio, B/C Ratio and marketing margin. The research results show that the average income of melon farmers per planting season is IDR 144,953,883 with an R/C Ratio of 6.12 and a B/C Ratio value of 5.12. Based on the results of the analysis, it is known that the Golden Alisha melon business is worth pursuing.